An alternative model for ERP maintenance strategy - Imtihan, Muhammad Rofi; Ngadiman, Mohd. Salihin; Haron, Habibollah (2008)
For the past few years, it has been possible to buy a business application including transaction processing systems for such tasks as accounting, manufacturing, or human resources as a packaged product. Packages to do this collection of work are generally referred to as Enterprise Resource Planning (ERP) systems. Most ERP systems are huge because of the diversity of tasks they must perform. The ERP systems are providing an integration of several tasks, and the flexibility to perform those tasks at enterprises with vastly varying needs. But, only few of these ERP systems developed have actually considered maintenance strategies. Maintenance is a complex process that is triggered by planned periodic repair (scheduled or planned maintenance), equipment breakdown or deterioration indicated by a monitored parameter (unplanned or emergency maintenance). This process includes planning, scheduling, monitoring, quality assurance and the development of necessary resources such as workshop, labor, machines, equipment, tools, spare parts and materials.